If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2t + 5 = -1 Reorder the terms: 5 + 2t = -1 Solving 5 + 2t = -1 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2t = -1 + -5 Combine like terms: 5 + -5 = 0 0 + 2t = -1 + -5 2t = -1 + -5 Combine like terms: -1 + -5 = -6 2t = -6 Divide each side by '2'. t = -3 Simplifying t = -3
| 44.88/103.524=x | | 2x^2+15=593 | | n*10=126 | | 3b+5=23 | | -125y^6+150y^5-45y^4=0 | | n+40=54 | | 86/2 | | 38/2 | | 3/x=15/25 | | -102-9x=-98-7x | | -8(4)= | | 25a^6+20a^5+4a^4=0 | | 6x+3y=1 | | -5(-7+5x)=-190 | | 5y-1+y+51=6y+50-2y | | -4(2p+4)-25=5(4p+3) | | 109x+17=77x+25 | | 5p+4=4p+11 | | 12x=204 | | 35+3y=110 | | 2t=7-1 | | -5e^6+5e^4=0 | | 2(c-3)=3(c-4) | | n+39=52 | | x+3y=110 | | -8x=120 | | 3(7-y)-y=5 | | -49+16y+9=4(5y-4)-4 | | 5(c-5)+4=2+c-23 | | 5x+9=51-10x | | -x-7=3x-7 | | 2-5x=10+3x |